Multimedia Technology in Physical Education Learning - Noor, Robby Dzulfaqor; Susilawati, Dewi (Sains Global Institut, Indonesia, 2024)
The role of educational technology in teaching is very important because of the use of information and communication technology. With the help of various applications for education, the Internet, teachers, and students themselves they see the advantages of educational technology without face-to-face. Physical education is a subject that currently does not allow for direct face-to-face meetings, this is where multimedia plays an important role. This study tries to provide an overview of the importance and use of multimedia technology in physical education. Article search using Google Scholar with the keyword Educational Technology published since 2020-2024. The conclusion of multimedia technology motivates students to work independently where students are more motivated to return to learning and working because modern technical equipment is widely available at all times.